The Financial Performance and Macroeconomic Factors Affecting Sharia Banking Market Share in Indonesia - Itsnaini Chusnul Khotimah; Novita Sari; Lita Ayudha Ningsih (Equity: Jurnal Ekonomi, 2023)
This research aims to find out which variables influence the sharia market share in Indonesia. This research is quantitative research with secondary data. The variables used in this research are financial performance with DPK, NPF, FDR and ROA indicators, as well as macroeconomic factors with indicators of inflation, interest rates and exchange rates. The sample for this research is the 2019-2023 Islamic banking monthly report. This research uses multiple linear regression analysis methods with partial tests (t tests), simultaneous tests (f tests) and coefficient of determination (R2). The results of this research are that DPK and the exchange rate have a significant effect on market share, while other variables NPF, FDR, ROA, Inflation & Interest Rates do not have a significant effect on market share.